Anton van Niekerk - Rasionaliteit en relaiivisme. Op soek na 'n rasionaliteitsmodel vir die menswetenskappe. 1992. Pretoria: RGN - Veuren, Pieter van (Koers, 1993)
This review article places Van Niekerk's book in the context of the current debate on rationality and relativism. The most important challenge which emerges from this debate is to develop a conception of rationality which neither reverts to an a-historical foundational ism nor succumbs to the temptation of relativism. Van Niekerk responds to this challenge by developing a hermeneutical model of rationality for the human sciences. My discussion of Van Niekerk’s book highlights his critique of relativism and his efforts to reconcile rationality and historicity. In evaluating his arguments for this reconciliation, I come to the conclusion that his efforts are beset by unresolved tensions.